Sowjetische Panzer und Militärs in den Strassen von Ost-Berlin. Aus: Illus, Sonderheft zum 1. Jahrestag des 17. Juni 1953
Sowjetische Panzer und Militärs in den Strassen von Ost-Berlin. Aus: Illus, Sonderheft zum 1. Jahrestag des 17. Juni 1953.